Effects of Surface Modification of Nanodiamond Particles for Nucleation Enhancement during Its Film Growth by Microwave Plasma Jet Chemical Vapour Deposition Technique - Chii-Ruey Lin; Da-Hua Wei; Minh-Khoa BenDao; Hong-Ming Chang; Wei-En Chen; Jen-Ai Lee (Advances in Materials Science and Engineering)
The seedings of the substrate with a suspension of nanodiamond particles (NDPs) were widely used as nucleation seeds to enhance the growth of nanostructured diamond films. The formation of agglomerates in the suspension of NDPs, however, may have adverse impact on the initial growth period. Therefore, this paper was aimed at the surface modification of the NDPs to enhance the diamond nucleation for the growth of nanocrystalline diamond films which could be used in photovoltaic applications. Hydrogen plasma, thermal, and surfactant treatment techniques were employed to improve the dispersion characteristics of detonation nanodiamond particles in aqueous media. The seeding of silicon substrate was then carried out with an optimized spin-coating method. The results of both Fourier transform infrared spectroscopy and dynamic light scattering measurements demonstrated that plasma treated diamond nanoparticles possessed polar surface functional groups and attained high dispersion in methanol. The nanocrystalline diamond films deposited by microwave plasma jet chemical vapour deposition exhibited extremely fine grain and high smooth surfaces (~6.4 nm rms) on the whole film. These results indeed open up a prospect of nanocrystalline diamond films in solar cell applications.